Agronomic and environmental dimensions of large-scale irrigation projects for sustainable agriculture - Gnanasekaran, M; Sellaperumal, P; Sivamurugan, A P; Dhanaraju, M; Selvaraj, S; Kaliaperumal, R; Vasumathi, V (Plant Science Today, 2025)
Across the world, large-scale irrigation projects (LSIPs) have revolutionized agriculture by ensuring food security and effective water resource management. Climate change including an increase in extreme weather events and altered rainfall patterns, has become a major challenge for the sustainability of agriculture. Thus, this paper deals with the prospects and concerns that revolve around LSIPs and urges the development of climate-resilient strategies. Sustainable water management strategies, water pricing, participatory irrigation management, technological inclusions like AI-, remote sensing- and IoT-based irrigation ensure precise and efficient water use. Hydrological models such as hydrologic engineering center-hydrologic modeling system (HEC-HMS), soil and water assessment tool (SWAT) and others help in understanding water resource dynamics. Case studies on China’s Three Gorges Dam, Egypt’s Aswan High Dam, Australia’s Murrumbidgee irrigation area and the Colorado river basin projects in the USA and Mexico reflect towering engineering feats and remarkable socio-economic transformations. While these infrastructures have advanced flood control, irrigation and hydropower generation, they have also highlighted the need for balanced development approaches that prioritize environmental integrity and social well-being. Thus, drawing from past lessons, integrating various adaptive management, community engagement and modern technologies and hydrological models are essential factors for sustaining agricultural productivity, water security and rural development in this rapidly changing and growing world.